Challenges in Management of Heart Failure and Chronic Kidney Disease in Primary Care Settings - Aloufi, Hanin Raja; Alotaibi, Felowah fares D; Almadani, Raneem Maher; Zamzami, Linah Zuhair; Algharbi, Abrar Mubarak A; Alruwaili, Amjad Hamoud; Alsalem, Wasan Siddiq; alrajeh, Maha Sultan Ahmed; Almukhlifi, Norah Hudyban; Shubayli, Ahmed Ali (Journal of Ecohumanism, 2024)
The management of heart failure (HF) and chronic kidney disease (CKD) in primary care settings presents unique challenges that can complicate patient outcomes. One of the significant hurdles is the complexity of coexisting conditions often seen in these patients, as heart failure and chronic kidney disease frequently co-manifest. This dual burden can lead to a vicious cycle, where the progression of one condition exacerbates the other. Primary care providers must navigate medication adjustments carefully, as many renally excreted drugs used in the management of heart failure may require dosage modifications in patients with CKD to avoid toxicity. Additionally, the overlapping symptoms of both conditions—such as fatigue, fluid overload, and dyspnea—can lead to misdiagnosis or under-treatment, further complicating the management strategies employed. Furthermore, the limited resources and time constraints typical of primary care settings pose significant barriers to effective management. Given the need for comprehensive assessments and interdisciplinary approaches in managing patients with heart failure and CKD, primary care providers may struggle to provide the level of individualized care that these complex patients require. Access to specialists, renal dietitians, and social workers can also be limited, making it difficult to implement multidisciplinary care plans that could enhance patient outcomes. Additionally, disparities in health literacy and socioeconomic factors can impede patient adherence to treatment regimens, follow-up appointments, and lifestyle modifications critical for managing both heart failure and CKD. These multifaceted challenges underscore the necessity for enhanced training, resources, and support systems within primary care to optimize the management of these prevalent and interacting conditions.